CORRELATES OF BODY COMPOSITION AND MOTOR PERFORMANCE VARIABLES OF UNIVERSITY OF ILORIN MALE HANDBALL PLAYERS - Tosho Surajudeen Bakinde (Universitas PGRI Semarang, 2021)
AbstractMotor performance is crucial for high-level performance in handball but the individual players' body composition determines the attainment of the enormous physical, psychological, technical and tactical demands required for team success. The study examined the correlates of body composition and motor performance variables of university of Ilorin male handball players. The descriptive correlational research design was adopted. All the 14 University of Ilorin male handball players were purposively selected for the study. Standardised instruments: non-elastic tape rule, weight scale, height scale, cones, whistle, measuring tape and stopwatch were used for data collection. Prior to data collection the weight scale and stopwatch were recalibrated while a pilot study was conducted to ascertain the reliability of the instrument. A Spearman rho of 0.89 was obtained as a confirmation of the instruments reliability. The data was analyzed using percentages, means, standard deviation and Pearson Product Moment Correlation at 0.05 alpha level. The study found moderate to high correlation of body composition with speed, agility and muscular endurance of University of Ilorin handball players. It was recommended that periodic assessment of body composition of the University of Ilorin male handball team should be included as part of the training requirement in other to maintain normal fat mass and fat-free mass for high-level performance.Key words: Fat mass, Whistle, Weight scale, Body Composition